2021
DOI: 10.1007/s10753-021-01569-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Baicalein in Brain Injury After Intracerebral Hemorrhage by Inhibiting the ROS/NLRP3 Inflammasome Pathway

Abstract: Intracerebral hemorrhage (ICH) is a devastating subtype of stroke with high disability/mortality. Baicalein has strong anti-in ammatory activity. This study aims to explore the mechanism of baicalein on brain injury after ICH. The model of brain injury after ICH was established by collagenase induction, followed by the evaluation of neurological severity, brain water content, the degenerated neurons, neuronal apoptosis and reactive oxygen species (ROS). The ICH model was treated with baicalein and silencing NL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…It was reported that in intracerebral hemorrhage brain injury model, ROS was elevated, and NLRP3 inflammasome pathway was activated [47]. It also reported that ROS scavenger may inhibit NLRP3 inflammatory response and alleviate brain injury [47]. Another study proved during ischemia/reperfusion injury, mitochondria malfunction caused ROS accumulation and stimulated NLRP3 inflammasome activation [48].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that in intracerebral hemorrhage brain injury model, ROS was elevated, and NLRP3 inflammasome pathway was activated [47]. It also reported that ROS scavenger may inhibit NLRP3 inflammatory response and alleviate brain injury [47]. Another study proved during ischemia/reperfusion injury, mitochondria malfunction caused ROS accumulation and stimulated NLRP3 inflammasome activation [48].…”
Section: Discussionmentioning
confidence: 98%
“…Although a variety of external or host-derived stimuli, such as mitochondrial dysfunction, ion flux, and lysosomal damage are involved in the activation of NLRP3 inflammasome [43], recent studies focused on mitochondrial autophagy and subsequent oxidative stress [44][45][46]. It was reported that in intracerebral hemorrhage brain injury model, ROS was elevated, and NLRP3 inflammasome pathway was activated [47]. It also reported that ROS scavenger may inhibit NLRP3 inflammatory response and alleviate brain injury [47].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, andrographolide significantly reduces the TNF-a and IL-6 levels by inhibiting the NF-kB signaling pathway (132). Other active ingredients in herbal medicine, such as verbascoside, cordycepin, and baicalein, inhibit inflammation and cell death and protect neurons following ICH by suppressing NLRP3 expression (136)(137)(138). Because of the common pharmacological actions, these drugs are likely to lessen pyroptosis after ICH.…”
Section: Direct Regulation Of Nlrp3mentioning
confidence: 99%
“…In addition, the presence of excessive ROS will directly cause the production of acute pro-inflammatory cytokines, including tumor necrosis factor α (TNF-α) and interleukin-10 (IL-10). ROS also can cause the activation of nuclear factor-κB (NF-κB), which has a critical role in promoting the inflammatory reaction ( Ma et al, 2014 ; Chen et al, 2022 ). During ICH-induced inflammation, the neutrophil activation causes damage to the respiratory chain, releasing excessive amounts of ROS and nitric oxide.…”
Section: The Role Of Oxidative Stress In the Pathophysiology Of Intra...mentioning
confidence: 99%